MSC-Exos: Important active factor of bone regeneration - Ren, Sihang; Lin, Yuyang; Liu, Wenyue; Yang, Liqun; Zhao, Muxin (Frontiers in Bioengineering and Biotechnology, 2023)
Bone defect and repair is a common but difficult problem in restorative and reconstructive surgery. Bone tissue defects of different sizes caused by different reasons bring functional limitations and cosmetic deformities to patients. Mesenchymal stem cells (MSC), a major hotspot in the field of regeneration in recent years, which have been widely used in various studies on bone tissue regeneration, and numerous studies have shown that the bone regenerative effects of MSC can be achieved through exosome-delivered messages. Although its osteogenic mechanism is still unclear, it is clear that MSC-Exo can directly or indirectly support the action of bone regeneration. It can act directly on various cells associated with osteogenesis, or by carrying substances that affect cellular activators or the local internal environment in target cells, or it can achieve activation of the osteogenic framework by binding to materials. Therefore, this review aims to summarize the types and content of effective contents of MSC-Exo in bone regeneration, as well as recent advances in the currently commonly used methods to enable the binding of MSC-Exo to the framework, and to conclude that MSC-Exo is effective in promoting osteogenesis.